PELATIHAN GURU SD MUHAMMADIYAH KALIWATES DALAM MENGELOLA LABORATORIUM IPA DAN PENGGUNAAN IPA KIT - Kukuh Munandar; Novy Eurika; Ika Priantari; Revyna Analika; Alifia Iffah Fajriyah; Sri Kantina (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
This community service activity was carried out with the aim of overcoming the obstacle of the lack of preparedness of teachers at Muhammadiyah Kaliwates Elementary School in managing science laboratories and operating basic science teaching aids. Through this training or technical guidance, teachers were equipped so that they could later manage science laboratories in elementary schools optimally. The methods used in this community service included providing classical technical guidance on laboratory management standards and hands-on training on the use of science teaching aids. The participants were eight teachers from Muhammadiyah Kaliwates Elementary School and one principal. The evaluation results showed a significant increase in the participants' cognitive understanding, as evidenced by an increase in the average score from 56.43 in the initial test to 82.86 in the final test. In addition, observations during the practical sessions showed that the educators were able to assemble and operate various science instruments independently, thereby boosting their confidence in designing inquiry-based learning. This activity was concluded to have successfully equipped educators with essential managerial competencies and instructional fluency. This capacity building directly prepared the school institution to welcome the operationalization of new science laboratory facilities to realize an applied and student-centered learning process.